Artificial Intelligence Based Pre-Marital Counselling Policy in Forming a Sakinah Family - Muhammad Sofyansah; Rahmatullah; Hildan Latif (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
This policy paper describes the policy of pre-marital counselling guidance based on artificial intelligence (AI) in forming a sakinah family. The purpose of this study is to analyse the implementation of an Artificial Intelligence (AI)-based pre-marital counselling policy as an innovative solution in preparing prospective married couples to form a sakinah family. The research also aims to identify the role of AI technology in detecting and preventing the main factors that cause divorce, such as disputes, arguments and economic problems, through the pre-marital counselling programme. This research uses descriptive qualitative methods to understand phenomena related to pre-marital counselling, the use of artificial intelligence (AI), and the formation of a sakinah family. Data sources consisted of primary data obtained through in-depth interviews with 15 respondents, and secondary data obtained from documentation studies, such as scientific literature and related policies. Data collection techniques included semi-structured interviews and documentation studies. The data analysis technique uses Miles and Huberman's interactive analysis model, which includes three stages: data condensation, data presentation, and conclusion drawing. This policy paper reveals that a policy that integrates AI in pre-marital counselling guidance with several concrete steps. Firstly, it is important for the government or relevant institutions to develop an AI-based digital platform that is easily accessible to prospective couples across Indonesia, with interactive features such as a chatbot for direct consultation. Second, the guidance programme should be tailored to the personal needs of each couple, by utilising AI algorithms that can assess and provide recommendations according to the couple's character and situation. Third, there needs to be continuous monitoring and evaluation of the effectiveness of the use of AI in this guidance, to ensure the quality of service remains optimal.